Current and past adherence to the World Cancer Research Fund/American Institute for Cancer Research recommendations in survivors of breast cancer - Emilia Kałędkiewicz; Dorota Szostak-Węgierek (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Breast cancer is the first in the structure of the incidence of neoplastic diseases in women, with the number of affected individuals becoming higher every year. The risk of breast cancer is influenced not only by genetic factors, but also by the lifestyle. Proper dietary habits, a high level of physical activity and normal body weight not only reduce the risk of developing a primary neoplastic lesion, but also a recurrence. In 2007 the World Cancer Research Fund (WCRF) and American Institute for Cancer Research (AICR) published their recommendations concerning lifestyle in the prophylaxis of neoplasms. Objective. The aim of the study was to assess whether the adherence to WCRF/AICR recommendations influenced the risk of developing breast cancer in women. Materials and methods. A case control study included 108 women aged over 50 with a history of breast cancer. The study group was divided into two subgroups: women who completed oncological treatment and experienced no recurrences for at least 5 years (group I, n=82) and women who had a recurrence (group II, n=26). The control group included women with no history of breast cancer (n=74). The adherence of lifestyle was assessed by assigning points for 8 WCRF/AICR recommendations. The results were compared in the study and control groups, both in all participants and separately in those who declared no changes in dietary habits after being diagnosed with breast cancer. Results. The adherence of lifestyle to WCRF/AICR recommendations was significantly lower in the group of women with a history of cancer compared to the control group. It was reported both in the study group as a whole (5.5 ± 1.34 vs 6.4 ± 1.48 points) and in those who declared no changes in dietary habits after being diagnosed with breast cancer (5.3 ± 1.24 vs 6.6 ± 1.38 points). The differences in the lifestyles of the participants with breast cancer and those in the control group were associated predominantly with the adherence to recommendations concerning appropriate physical activity, avoiding the consumption of sweetened drinks and limiting the consumption of processed and red meat. Conclusions. The results of the study confirmed the benefits of complying with WCRF/AICR recommendations in the prevention of breast cancer.